Case report: Radiographic complete response of radiation-induced glioblastoma to front-line radiotherapy: A report and molecular characterization of two unique cases - Grogan, Patrick T.; Helgager, Jeffrey J.; Deming, Dustin A.; Howard, Steven P.; Jenkins, Robert B.; Robins, H. Ian (Frontiers in Neurology, 2023)
Radiation-induced gliomas (RIGs) are an uncommon disease type and a known long-term complication of prior central nervous system radiation exposure, often during childhood. Given the rarity of this malignancy subtype, no clinical trials have explored optimal therapy for these patients, and the literature is primarily limited to reports of patient cases and series. Indeed, only recently have the genomic profiles of RIGs been explored in limited numbers, categorizing these gliomas into a unique subset. Here, we describe two cases of RIG, diagnosed as glioblastoma (GB), IDH-wildtype, in adults previously managed with central nervous system radiation for childhood cancers. Both patients demonstrated surprising complete radiographic response of postoperative residual disease to front-line therapy, a phenomenon rarely observed in management of any GB and never previously reported for the radiation-induced subgroup. Both tumors were characterized by next generation sequencing and chromosomal microarray to identify potential etiologies for this response as well as to further add to the limited literature about the unique molecular profile of RIGs, showing signatures more consistent with diffuse pediatric-type high-grade glioma, H3 wildtype and IDH-wildtype, WHO grade 4. Ultimately, we demonstrate that treatment utilizing a radiation-based regimen for GB in previously radiated tissue can be highly successful despite historical limitations in the management of this disease.